Adaptation in Gait to Lunar and Martian Gravity Unloading During Long-Term Isolation in the Ground-Based Space Station Model - Saveko, Alina; Brykov, Vitaly; Kitov, Vladimir; Shpakov, Alexey; Tomilovskaya, Elena (Frontiers in Human Neuroscience, 2022)
The aim of the experiment was to evaluate the adaptive responses of biomechanical and electromyographic parameters to vertical unloading (Lunar – 0.15 G and Martian – 0.35 G) when walking during the 4-month isolation experiment SIRIUS-19 in the ground-based space station model (GBI). The study involved 6 healthy international crew members of the SIRIUS-19 project aged 34±6.2 years (3 women and 3 men). Body Weight Unloading (BWU) conditions was created by the h/p/cosmos airwalk system. The locomotor test included walking (3.5±0.3 km/h) with a sequential change of BWU modes: 5-minute walking with 0% BWU (1 G), 5-minute walking with 65% BWU (0.35 G) and 5-minute walking with 85% BWU (0.15 G). Ground Reaction Force was recorded by the h/p/cosmos treadmill device. Muscle Lab Model 4000e device was used to record the electromyographic signals of the hip and shin muscles. The locomotor test was performed twice before GBI, monthly during GBI and one week after leaving isolation. The results obtained before GBI demonstrate that the changes of support and proprioceptive afferentation signals play significant role in reorganizing of the biomechanical structure of motor acts and the development of new movement patterns. The results of the study are consistent with the previously obtained results of other studies in this direction. Despite the fact that during the GBI the participants of the experiment performed regular physical training, a decrease in the performance indicators values was detected, especially pronounced after 100 days of GBI. This is probably due to limited space of a space station model, as well as the development of a special motor stereotype in it. Noteworthy are the results obtained after the 4th session of the experiment, indicating the effect of sensorimotor learning. We think that the data obtained in this study will be useful in research both in gravitational physiology and in clinical medicine. The study is supported by the Russian Academy of Sciences (63.1).